Pascere Dominicum gregem: L’ecclesiologia come chiave d’accesso alla teologia pastorale di Giacomo Biffi - Pinna, Samuele (Alpha omega, 2018)
According to Benedict XVI, Giacomo Biffi, «with his extraordinary intelligence and with his cultural and theological formation, associated with a good dose of humour, [...] was completely at the service of truth, of the Lord and so of the people of our time». The present study intends to offer a synthetic overview of his theology, including of his pastoral theology, keeping in mind both the richness of his thought and also its concrete implementation by him personally, insofar as he was, in the words of Francis, «a concerned and a wise leader». For this reason, we have tried to bring out its ecclesiological foundations, as the key to being able to grasp his vision of pastoral theology, such as to make possible its practical implementation, on the basis of those principles which Cardinal Biffi considered to be of fundamental importance.